The Big Catch-up: Addressing Zero-Dose Children as a Surrogate of Vaccination Disruptions During Public Health Emergencies - Sadaf Khan; Gajendra Kumar Gupta; Deepika Agrawal; Syed Hasan Nawaz Zaidi; Jyoti Batra; Sabin Syed; Lokesh Sharma; Maureen Khambira; Dereje Ayalew Haile; Ghanshyam Sethy; Snehil Kumar Singh (European Scientific Journal, ESJ, 2024)
The COVID-19 pandemic has significantly disrupted global immunization programs, resulting in a sharp increase in the number of zero-dose children-those who have not received any vaccinations. This disruption poses a critical threat to public health, exacerbating the risk of vaccine-preventable disease outbreaks. This paper investigates the pandemic's impact on routine childhood immunization, with a particular focus on zero-dose children. Through a comprehensive review of data from WHO, UNICEF, Gavi, and key informant interviews, we highlight evidence-based interventions aligned with the strategic framework of the Zero Dose Guidelines. Our findings emphasize the importance of context-specific approaches, particularly in vulnerable settings such as urban slums, remote rural areas, and conflict zones. We identified key thematic areas for intervention: community engagement, health systems strengthening, and technological innovations. These strategies are critical for reaching zero-dose children and rebuilding resilient immunization systems. However, gaps remain in the evidence surrounding the long-term effectiveness and cost-efficiency of these interventions, especially in low- and middle-income countries. This study underscores the urgency of addressing the growing number of zero-dose children through coordinated global efforts like "The Big Catch-Up" campaign, which aims to recover and strengthen immunization coverage worldwide. By focusing on equity, innovation, and tailored strategies, we can mitigate the pandemic’s long-term effects and ensure that no child is left unprotected.